The spiritual journey of Robinson Crusoe through the lens of the Qur’an - Tareq Zuhair (Cogent Arts & Humanities)
All religions stem from one source, which is God. Religious teachings have stressed the importance of abhorring sins to avoid punishment and pursuing virtues to achieve happiness and success. As a dissenter, Daniel Defoe, the author of Robinson Crusoe (1719), intended to guide humans to these teachings through the title character. This paper investigates how the lessons experienced by Crusoe in certain incidents and documented in his diary are similar in context to some stories narrated in the Qur’an about people who share with Crusoe the experience of navigating a spiritual journey that passes through the cycle of punishment and reward when deviating from or following divine guidance.